Efektivitas Game RPG Maker MV dalam Edukasi Lingkungan pada Siswa Sekolah Dasar - Amalia Putri Mardani; Tiara Choirundhini Mawardi; Muhammad Iqbal Hanafri; Eka Uliyanti Putri Br Bangun (Progresif: Jurnal Ilmiah Komputer, 2025)
Interactive 2D educational game based on RPG Maker MV is an innovative learning media that combines the concept of role-playing game (RPG) with educational material to create an interesting learning experience. The development of digital technology encourages the transformation of education, one of which is through interactive and accessible educational games. This research developed an environmental-themed game for elementary school students using the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC) method, which includes six stages: concept, design, material collection, manufacture, testing, and distribution.  Based on the calculation of the feasibility level, the level of respondent satisfaction obtained from filling out the questionnaire reached 91.81% of the total 40 respondents. This finding proves that this 2D educational game is effective in increasing learning motivation, understanding environmental concepts, and fostering positive student behavior. Thus, the development of RPG Maker MV-based games using MDLC can be an innovative solution to create more interactive and effective learning at the elementary school level.Keywords: 2D educational game; RPG Maker MV; Environmental awareness; Elementary school.   AbstrakGame edukasi 2D interaktif berbasis RPG Maker MV adalah media pembelajaran inovatif yang menggabungkan konsep Role-Playing Game (RPG) dengan materi edukasi untuk menciptakan pengalaman belajar yang menarik. Perkembangan teknologi digital mendorong transformasi pendidikan, salah satunya melalui game edukasi yang interaktif dan mudah diakses. Penelitian ini mengembangkan game bertema lingkungan untuk siswa SD menggunakan metode Multimedia Development Life Cycle (MDLC) versi Luther-Sutopo, yang meliputi enam tahap: konsep, desain, pengumpulan bahan, pembuatan, pengujian, dan distribusi.  Berdasarkan hasil perhitungan tingkat kelayakan, tingkat kepuasan responden yang diperoleh dari pengisian kuesioner mencapai 91,81% dari total 40 responden. Temuan ini membuktikan bahwa game edukasi 2D ini efektif dalam meningkatkan motivasi belajar, pemahaman konsep lingkungan, dan menumbuhkan perilaku positif siswa. Dengan demikian, pengembangan game berbasis RPG Maker MV menggunakan MDLC dapat menjadi solusi inovatif untuk menciptakan pembelajaran yang lebih interaktif dan efektif di tingkat sekolah dasar.Kata kunci: Game edukasi 2D; RPG Maker MV; Kepedulian lingkungan; Sekolah dasar.